A multivariate model to estimate environmental load on an offshore structure. (15th April 2023) - Ramadhani, Adhitya; Khan, Faisal; Colbourne, Bruce; Ahmed, Salim; Taleb-Berrouane, Mohammed
Abstract: Offshore structures such as oil platforms are subjected to significant environmental loads caused by wind, waves, and current. The complexity of offshore environment requires robust and reliable models to capture dependencies among environmental variables. A vine copula is a powerful tool that can be used to construct multivariate models by decomposing the complex structure into a series of simple pair copulas. Previous studies have shown that simple and symmetric copulas can be used as building blocks to construct vine copula models. In this study, symmetric and asymmetric copula functions are considered building blocks to capture all possible dependency structures. The c-vine model is then used to estimate the total environmental load on an offshore structure. Estimated loads are compared with those using the traditional independent variable approach and a multi-Gaussian distribution function-based method. The results reveal that both symmetric and asymmetric copula functions can be fitted to build c-vine copula models for the trivariate case. C-vine copulas, constructed using asymmetric copulas, provide a better estimation of the total environmental load than the independent and multivariate Gaussian methods. The result of this study is useful in probabilistic structural analysis of offshore structures for design and resilience analysis. Highlights: Study investigates offshore structure response to multivariate load using C-vine Copula. Dependence between wind velocity, current and wave height is considered for load modelling. Offshore structure to be designed considering asymmetrically dependent loads.